PENGARUH KERAGAMAN BELANJA TERHADAP KETIMPANGAN PENDAPATAN ANTAR DAERAH DI PROVINSI JAMBI - Wiyan Mailindra (Universitas Batanghari Jambi, 2017)
The purpose of this study was to determine income inequality and the effect diversity of expense toward income inequality in the period 2005-2015. The analysis method used quantitative analysis with Williamson Index analysis and simple regression, the date got from ten districts in jamby province. The results this study showed income inequality between regions during the period has category medium inequality,the variety of region expense has effect positive significant to income inequality level. Conclusion this study was the higher level of diversity of expense will be increase income inequality between regions. The policy implication of this research was develop the economic development center that taked to the potential of each region by utilizing resources in the region so that the level of income inequality between regions is not too high.Keywords : diversity of expense, income inequality, economic development, potential of region.